No Solid Colloidal Carriers: Aspects Thermodynamic the Immobilization Chitinase and Laminarinase in Liposome - Alonso-Estrada, Dania; Ochoa-Viñals, Nayra; Pacios-Michelena, Sandra; Ramos-González, Rodolfo; Núñez-Caraballo, Arianna; Michelena Álvarez, Lourdes Georgina; Martínez-Hernández, José Luis; Neira-Vielma, Alberto Antonio; Ilyina, Anna (Frontiers in Bioengineering and Biotechnology, 2022)
The present review describes the basic properties of colloidal and vesicular vehicles that can be used for immobilization of enzymes. The thermodynamic aspects of the immobilization of enzymes (laminarinase and chitinase) in liposomes are discussed. These systems protect enzymes against environmental stress and allow for a controlled and targeted release. The diversity of colloidal and vesicular carriers allows the use of enzymes for different purposes, such as mycolytic enzymes used to control phytopathogenic fungi.